Economic potential of flexible balloon biogas digester among smallholder farmers: A case study from Uganda. (May 2018) - Kabyanga, Moris; Balana, Bedru B.; Mugisha, Johnny; Walekhwa, Peter N.; Smith, Jo; Glenk, Klaus
Abstract: Biogas technology, as a pro-poor renewable energy source, has been promoted in Uganda since the 1980s by the government and NGOs. However, many of the biogas designs promoted have proved to be too expensive for the average Ugandan to afford. A cheaper flexible balloon digester has been proposed, but there have been lack of evidence on the economic viability of this design. The purpose of this study was to analyze the economic potential of a flexible balloon digester among smallholder farmers in Uganda using the tool of cost-benefit analysis. Primary data were obtained from survey of experimental households and 144 non-biogas households in central Uganda. The results revealed that the net present value was negative and the payback period was greater than the economic life of the digester. However, sensitivity analysis revealed that with a 50% reduction in investment cost the technology is financially viable for 67% of the households and to all households as a group (NPV= UGX5, 804, 730). The initial investment cost is a critical factor to economic viability and potential technology adoption. We suggest that government and development partners interested in the sector should consider strategies that could reduce the technology cost, for example, by manufacturing low cost balloon digester locally instead of importing prefabricated digesters. Highlights: We analyzed the economic potential of flexible balloon biogas design in Uganda. We used the tool of cost-benefit analysis using survey data from smallholder farmers. Households prefer to shift from fuelwood and kerosene to biogas for cooking and lighting. Investing in flexible balloon digester is not viable financially to smallholder farmers.